PENGARUH STRATEGI PEMASARAN TERHADAP KESEJAHTERAAN KARYAWAN HOME INDUSTRY TEMPE RISMANTO DI KELURAHAN RAJAWALI KOTA JAMBI - Rezeki, Yuvita Sri; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2021)
AbstractThis study aims to find out (1) To describe the marketing strategy of Rismato's tempeh home industry in Rajawali Village, Jambi City. (2) To find out the description of the welfare of the Tempe Rismanto home industry employees in Rajawali Village, Jambi City. This research design uses quantitative research methods, with data collection techniques through observation (observation), questionnaires (questionnaire), and interviews. Where the population in this study were 30 respondents with a sample of 30 respondents. The research instrument test technique used in this study is the Validity and Reliability Test, while the classical assumption test used is Descriptive Analysis, Normality Test, Homogeneity Test, and Simple Regression Test, while this Hypothesis Test is Partial Test. The results of this study indicate that (1) The marketing strategy is included in the fairly good category with the achievement of an average TCR value of 78.10%. (2) Employee welfare is in the good category with an average TCR score of 81.90%. That is, the marketing strategy has a strong influence on a product to be marketed, while the welfare of employees is remuneration provided directly or indirectly to improve the financial condition of employees, and with a marketing strategy it can increase income and affect employee welfare.Keywords: Marketing Strategy, Employee Welfare.